Genotype-phenotype correlation in a cohort of pediatric patients with autoinflammatory diseases carrying NOD2 variants - Natale, Marco Francesco; Celani, Camilla; Federici, Silvia; Passarelli, Chiara; Perrone, Chiara; Marasco, Emiliano; De Benedetti, Fabrizio; Insalaco, Antonella (Frontiers in Immunology, 2025)
BackgroundAutoinflammatory diseases (AIDs) are a group of disease characterized by excessive activation of the innate immune system with episodes of spontaneous inflammation that can affect different organs. Many monogenic or acquired autoinflammatory diseases are described in literature. More recently the concept of disease with polygenic or complex inheritance has been introduced. Nucleotide binding oligomerization domain containing 2 (NOD2) gene variants are associated with Crohn’s disease (CD), Blau syndrome and most recently with a polygenic autoinflammatory disease with onset in adult called NOD2-associated autoinflammatory disease (NAID).ObjectiveThe aim of our study is to describe a pediatric cohort of patients with autoinflammatory disease carrying NOD2 variants and to evaluate genotype-phenotype correlation.MethodsTwenty-five children with autoinflammatory disease and NOD2 variants were enrolled in the study. Patients were divided into 3 groups based on the protein domain involved. Demographic and clinical features, imaging, laboratory exams and treatment were analyzed. The characteristics of our patients were compared with those of the adult cohort described by Yao in 2016-2018.ResultsFever was the main clinical characteristic of our children (68%) with long episodes and irregular pattern of recurrence. The disease typically affected skin (40%), joints (72%), bowel (60%) and lymphatic system (52%). Serositis and sensorineural deafness were less frequent. Excluding non-steroidal anti-inflammatory drugs (NSAIDs), glucocorticoids were frequently used with satisfactory clinical response in the majority of patients. In patients with poor disease control or new flares after glucocorticoid tapering, non-biologic and biologic drugs were used with variable response. The comparison between the two most represented groups showed that patients with variants located on the NOD domain presented more homogeneous clinical characteristics with involvement of some target organs. Our patients were compared with the adult cohort described in literature with few differences.ConclusionThis is the first study to evaluate genotypic/phenotypic characteristics of children with systemic autoinflammatory disease and NOD2 variants. The results, albeit preliminary and affected by the sample size, do not allow a definitive conclusion on a monogenic disease caused by mutation in NOD2, with the obvious exception of Blau syndrome. Variants in the NOD domain seem to be associated with a more homogenous clinical phenotype.